Exploring Trends in Education Program Evaluation Models in High Schools: Bibliometric Analysis - Mariano Dos Santos; Ahmad Ahmad (PT. Pusmedia Group Indonesia, 2025)
This study aims to analyze the program evaluation model applied in high school using a bibliometric approach integrated with interpretive analysis. The main problem identified was the importance of understanding the various evaluation models that are often applied in education and their influence on improving the quality of the program. The method used in this study is a bibliometric analysis by selecting 120 articles published between 1985 and 2024 from the Scopus database related to the evaluation of educational programs in secondary schools. Data was collected through a search for articles with relevant keywords, and an analysis was conducted to find thematic trends and collaborations between authors in this field. Data were analyzed using the prism method and the R Studio application with the Bibliometrix::biblioshiny() package to explore thematic trends, author collaboration networks, and conceptual structures. The results show that evaluation models, such as the Outcome-Mediation Cascade (OMC), TADIPHE, and EP_PISTdu, are increasingly relevant in complex educational contexts. The study also found the importance of gender elements in program evaluation, with a focus on equality between women and men. In addition, international collaborations between authors from different countries, such as the United States and Canada, are instrumental in enriching the quality of program evaluation research. This study suggests that the development of more innovative and relevant evaluation models should be carried out to increase the effectiveness of educational program evaluations in the future.